Przezskórna elektrostymulacja nerwów (TENS) w leczeniu zespołów bólowych kręgosłupa lędźwiowo-krzyżowego = Transcutaneous electrical nerve stimulation (TENS) in the treatment of low back pain - Weber-Rajek, Magdalena; Kowalska, Monika; Radzimińska, Agnieszka; Strączyńska, Agnieszka; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Weber-Rajek Magdalena, Kowalska Monika, Radzimińska Agnieszka, Strączyńska Agnieszka, Zukow Walery. Przezskórna elektrostymulacja nerwów (TENS) w leczeniu zespołów bólowych kręgosłupa lędźwiowo-krzyżowego = Transcutaneous electrical nerve stimulation (TENS) in the treatment of low back pain. Journal of Education, Health and Sport. 2016;6(3):11-20. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47232 http://ojs.ukw.edu.pl/index.php/johs/article/view/3415 https://pbn.nauka.gov.pl/works/718828 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. Przezskórna elektrostymulacja nerwów (TENS) w leczeniu zespołów bólowych kręgosłupa lędźwiowo-krzyżowego Transcutaneous electrical nerve stimulation (TENS) in the treatment of low back pain Magdalena Weber-Rajek1, Monika Kowalska2, Agnieszka Radzimińska1, Agnieszka Strączyńska1, Walery Zukow3 1 Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy Katedra Fizjoterapii, Bydgoszcz, Polska / Nicolaus Copernicus University in Toruń, Collegium Medicum in Bydgoszcz, Department of Physiotherapy, Bydgoszcz, Poland 2 Bydgoska Szkoła Wyższa, Bydgoszcz, Polska / University of Bydgoszcz, Bydgoszcz, Poland 3 Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska / Kazimierz Wielki University, Bydgoszcz, Poland Streszczenie Wstęp Bóle kręgosłupa lędźwiowo-krzyżowego są poważnym problemem medycznym i społecznym. Fizjoterapia jest nieodzownym elementem leczenia zespołów bólowych kręgosłupa. Metodą, która zdobywa coraz większe uznanie wśród fizjoterapeutów, a także wśród pacjentów jest stymulacja TENS (transcutaneus electrical nerve stimulation). Cel badań Celem niniejszej pracy była ocena skuteczności terapii TENS w terapii zespołów bólowych kręgosłupa lędźwiowo-krzyżowego. Materiał i Metody Badania przeprowadzono w grupie czterdziestu pacjentów w wieku 30 - 60 lat (średnia wieku 45 lat). Bezpośrednio przed oraz po zakończeniu terapii u wszystkich pacjentów wykonano: ocenę dolegliwości bólowych przy użyciu skali VAS, ocenę natężenia i częstotliwości bólu, ilości stosowanych leków przeciwbólowych, ograniczenia aktywności ruchowej przy użyciu kwestionariusza Laitinena, test Schobera oceniający zakres zgięcia kręgosłupa lędźwiowo-krzyżowego. Analizę statystyczną przeprowadzono wykorzystując pakiet PQStat wersja 1.4.8. Normalność rozkładu zmiennych sprawdzano testem Shapiro-Wilka. W celu porównania wyników otrzymanych w testach przed terapią z wynikami otrzymanymi po terapii przeprowadzono test Wilcoxona na poziomie istotności α = 0,05. Wyniki Uzyskano istotne statystycznie zmniejszenie intensywności i częstotliwości bólu, zmniejszenie ilości stosowanych leków przeciwbólowych, zmniejszenie ograniczenia aktywności ruchowej oraz zwiększenie zakresu zgięcia kręgosłupa lędźwiowo-krzyżowego. Wnioski Stymulacja TENS jest skutecznym zabiegiem w leczeniu zespołów bólowych kręgosłupa lędźwiowo-krzyżowego. Słowa kluczowe: przezskórna stymulacja nerwów (TENS), zespoły bólowe kręgosłupa lędźwiowo-krzyżowego. Summary Introduction Low back pain is a serious medical and social problem. Physiotherapy is the indispensable component of treatment of back pains. A method that is gaining more recognition among physiotherapists, as well as among patients is the transcutaneus electrical nerve stimulation (TENS). Aim of the study The aim of this study was to evaluate the effectiveness of TENS in the treatment of low back pain. Material and Methods Study included of forty patients aged 30 - 60 years (mean age 45 years). Immediately before and after therapy in all patients: assessment of pain using the VAS assessment of pain intensity and frequency, amount of applied analgesics, limiting physical activity using a questionnaire Laitinen, Schober test assessing the scope bending lumbosacral spine. Statistical analysis was performed using version 1.4.8 PQStat package. In order to compare the results obtained in the test prior to treatment with the results obtained after treatment was Wilcoxon test at the significance level α = 0.05. Results Achieved a statistically significant reduction in the intensity and frequency of pain, reduction of applied analgesics, reduced physical activity limitations and increasing the range of flexion of low back pain. Conclusion TENS is an effective treatment for both acute and chronic low back pain Key words: transcutaneous electrical nerve stimulation, low back pain.